Strengthening Teachers’ Digital Literacy through Interactive Video Making Training using the Kinemaster Application - Wahyu Kyestiati Sumarno; Hendrik Furqon; Ali Shodikin; Nur Imro’atus Solikha; Novandi Kevin Pratama; Didan Rizky Adha (Nusantara Science and Technology Proceedings, 2022)
Digital literacy is one of the important literacies that needs to be developed at schools, both by teachers and students. Teachers’ low mastery of digital literacy will certainly hinder the students’ achievements during the teaching and learning process. Therefore, it is important for teachers to actively participate in updating themselves on digital developments, including the use of making interactive learning videos. The purpose of this program is to strengthen the digital literacy of teachers through interactive learning videos making training using the Kinemaster application. The methods used in this training were training and mentoring, assignments, and workshop results. It was previously confirmed that prior to this training, the trainee teachers had never known and used the Kinemaster application to make learning videos. The result of this activity is that 85% of teachers have understood and are able to use the Kinemaster application to make interactive learning videos. From the workshop, as many as 75% of teachers were able to complete the making of simple learning videos properly and on time.